Public Knowledge of Cardiovascular Diseases and its Risk Factors in Jeddah City, Saudi Arabia - Ahmed, Shereen Helmy; Bokhari, Yumna Abdulmalek; Nahas, Rana Jamal; Alharbi, Amjad Zaki; Niyazi, Asrar Abdullah; AlGaedy, Renad Abdulwahab (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Cardiovascular diseases (CVDs) are one of the critical yet preventable non-communicable diseases. Based on the World Health Organization (WHO) reports on non-communicable conditions in 2010, millions of people were killed by non-communicable diseases in 2008, resulting in deaths that occurred before the age of 60 (1). Our aim in this study is to provide descriptive epidemiology and to estimate the public’s knowledge towards CVD types, risk factors, and warning symptoms of heart attack or stroke. Methodology: The study was approved by Ibn Sina National College of Medical Sciences research committee in November of 2019.This is a cross-sectional analytic study conducted among the Saudi community in Jeddah City, Saudi Arabia from November 2019 to April 2020. A total of 635 respondents contributed to fill the self-administered questionnaire. Statistical package for social sciences (SPSS) version 20 was used. The degree of association was tested using Chi-square. A statistically significant association was taken at P<0.05. Results: Participants who agreed to participate consisted of 228(35.9%) males and 407(64.1%) females. Hypertension is the highest disease diagnosed with a total of 111(17.5%) and highest among females with 71(64.0%). Most of the participants identified chest pain and discomfort (76.4%) and shortness of breath (73.7%) as symptoms of heart attack. Compared with other symptoms such as pain or discomfort in the arm or shoulder (57.3%), weakness in the arm or leg on one side of the body (55.6%), and weakness lightheaded and fainting (51.2%). Conclusion: The study participants show low knowledge in CVS. There is a need to increase public awareness and to establish basic knowledge to the general and targeted individuals.